Developing a methodology to model and predict the grinding performance of the dry stirred mill. (1st August 2019) - Altun, Deniz; Altun, Okay; Zencirci, Sarp
Highlights: Focus was given on fine particle breakage. Various methodologies of particle breakage characterization techniques were investigated. Development of a methodology to model a continuous dry horizontal stirred mill was aimed. Abstract: This study aims to evaluate the use of different particle breakage characterization methodologies in modelling of a dry horizontal stirred media mill. Within the context, Hardgrove mill and drop weight tester were utilized on granulated blast furnace slag, coarse cement, finished cement, filter return and fly ash samples. As a result of the experimental works undertaken at different size intervals and energy levels, the appearance functions of each sample were calculated by using the correlation between specific comminution energy and t10 values or fines' generation. Calculated appearance functions were inputted to the perfect mixing model and r/d values were back-calculated. In this regard, the feed and product data from the comminution tests of a pilot scale dry stirred mill was used. When the plots of r/d data were compared, it was found that both Hardgrove and impact bed breakage tests lead to having good agreement between the experimental and calculated product size distributions. Consequently, the later stage of the study focused on the development of a modelling for the dry stirred mill by using the breakage function from Hardgrove mill, which was found convenient and easier.